Pengaruh Olahraga untuk Mencegah Osteoporosis terhadap Kepadatan Mineral Tulang pada Wanita Usia 25-35 Tahun - Suwarno, Susetyo; Suwarno, Bagus Syahbuddin Susetyo; Suwarno, Dimas Rafif Susetyo (Institut Teknologi Bandung, 2024)
Reports of surveys on exercises that can increase bone mineral density (BMD) have already been proven in many studies. One of the efforts to organize formal physical exercise for every level of society is the formation of Senam Pencegahan Osteoporosis (SPO) - Physical Exercise to Prevent Osteoporosis. Is SPO able to increase BMD for women aged 25-35 years? A total of 46 healthy young women ranging from 25 -35 years of age who had never done or even were not involved in any exercise before the time of the study were divided into two groups (23 experimental and 23 control participants) and volunteered to proceed a three times a week of this exercise for 3,5 months. BMD was measured by using Dual Energy X-ray Absorptiometry (DEXA). A significant increase of BMD in the ulna, vertebral lumbar 2, and vertebral lumbar 1-2 was detected in the experimental group. There is a strong indication that SPO can increase BMD, especially in the ulna, which has a high risk of osteoporosis.